Three new species of Begonia sect. Baryandra from Panay Island, Philippines - Ching-I Peng; Rosario Rivera Rubite; Che-Wei Lin; Mark Hughes; Yoshiko Kono; Kuo-Fang Chung (Botanical Studies, 2017)
Abstract Background The flora of Panay Island is under-collected compared with the other islands of the Philippines. In a joint expedition to the island, botanists from Taiwan and the Philippines found three unknown Begonia species and compared them with potentially allied species. Results The three species are clearly assignable to Begonia sect. Baryandra which is largely endemic to the Philippines. Studies of literature, herbarium specimens, and living plants support the recognition of the three new species: Begonia culasiensis, B. merrilliana, and B. sykakiengii. Somatic chromosomes at metaphase were determined to be 2n = 30 for B. culasiensis and 2n = 28 for both B. merrilliana and B. sykakiengii, congruent with those of most species in sect. Baryandra. Molecular phylogenetic evidence is consistent with B. culasiensis being a relict from the late Miocene and B. merrilliana and B. sykakiengii being younger species of Pleistocene origin. Conclusion The continuing discovery of endemic Philippine species means the remaining fragments of both primary and secondary native vegetation in the archipelago are of increasing value in terms of natural capital. A secure future for the species could be realized through ex situ conservation collections and raising awareness with community groups.